IP@Remote : intelligent photography remote (with Arduino & Android) - Wong, Jasmine Zhen Ying (2017)
High-speed photography is the art of the capturing an image of a specific moment in an occurrence that happens extremely quick, typically less than a second. In the commercialized market of high-speed photography peripherals, there is a range of device targeted mainly at scenarios that involve sound, light and laser sensors. Despite the existence of water droplet photography kit, the majority of the commercialized kits are sold as an individual set of the system. This project aims to enhance and maintain the features of the previous project to accommodate the integration of a water droplet system. The focus of the project is heavily concentrated on the design and implementation of a water droplet system that renders assistance to the user in achieving realistic expectations in the art of water droplet photography. Through the harmonization of hardware and software implementation based on the respective Arduino and Android platform, precise water droplet manipulation provides the possibility for achieving greater heights in the production of water droplet photography art.